Comparing a Combination of Saline and Chlorhexidine with Saline as Root Canal Irrigation Solutions in Pulpectomy of the Primary Molars in 6-9 Years Old Children, A Double Blind Clinical Trial - Mahsa Sayadizadeh; Raziyeh Shojaeipour; Masoumeh Aminizadeh; Azadeh Horri; Sajad Raeisi Estabragh; Mohammadjavad Aminizadeh; Farzane Jalali (Mashhad University of Medical Sciences, 2019)
Introduction: Using irrigation solutions in pulpectomy procedures for children is the best technique to dissolve and remove the soft necrotic materials during instrumentation. Normal saline solution (NSS) has no antibacterial activity and only results in root canal cleaning during irrigation. The 2% chlorhexidine gluconate (CHX) solution significantly decreases bacterial colonies, compared to NSS. The present study was performed to evaluate the success of irrigation by NSS and CHX combined solution, in comparison to NSS. Materials and Methods: The current study was conducted on 60 children aged 6‒9 years allocated to the two groups of test and control. All the participants had one primary molar tooth with signs and symptoms of irreversible pulpitis. During pulpectomy of the 30 teeth, the standard technique, consisting of irrigation with 0.9% NSS was used for the control group. The 30 teeth of the remaining subjects in the case group were irrigated with an equal volume of 0.2% CHX and NSS combination. Clinical radiographic follow-ups were scheduled at 6 and 12 month post-operation intervals. Results: The success rates at 12 month follow-up from clinical and radiographic viewpoints in the control group were 83% and 73%, respectively. For the case group, success rates of 97% and 90% were reported clinically and radiographically, respectively. There were no significant diffferences between the case and control groups at 6- (P= 0.492) and 12- (P= 0.195) month clinical follow-ups.     On the other hand, the two groups were siginificantly different regarding the 6-month radiographic follow-up (P=0.038); however, such difference was not significant at the 12-month follow-up (P=0.095). Conclusion: Theone-year follow-up showed that there is no diffference between CHX and NSS as irrigation solutions for cleaning the root canals of primary teeth with irreversible pulpitis.